Значення малої Батьківщини для формування патріотичних почуттів (на прикладі творчості Василя Сухомлинського) - Заячківська, Надія (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2021)
Nowadays there is increased attention to patriotic education as an essential component of patriot citizen formation in Ukraine. The article reveals the importance of a homeland for the formation of patriotic feelings among pupils on the example of Vasyl Sukhomlynskyi’s creative work. A prominent Ukrainian educator believed that the basis of love for the Motherland is the nature of the native land, the mother tongue, the cult of a Mother and a Father, diligence, as well as the homeland, its historical and heroic past. Patriotic feelings are formed from early childhood from the perception of the image of a homeland – streets, villages, towns, cities, native land, and close surroundings. According to V. Sukhomlynskyi, at a very young age, the child’s soul is susceptible to emotional influences; it admires what she/he sees, as well as the beauty of the land her/his grandparents and great-grandparents lived on.The effectiveness of patriotic education for teenagers and adolescents depends on how deeply the image of the homeland penetrated the younger schoolchildren’s the spiritual world. A school, a teacher, and the mother tongue are also of great importance in this process. The patriotic vision of the world be-128gins with the love of its homeland and develops into the love of the Motherland – Ukraine and all humanity.
Keywords: homeland; patriotism; patriotic feelings; Vasyl Sukhomlynskyi’s creative work